Exportações e crescimento: um teste de causalidade para o caso chileno - Ribeiro, Talita Miranda (2008)
The present work aims to investigate the impact of exports in the Chilean economic growth from the recovery of the debt crisis in middle of the 1980s. The developed analysis was given around three main controversies: the causality between international trade, particularly exports, and economic growth, the paper of the diversification of the exporting guideline in this process and the different effect of the ore exports and industrial goods. For this purpose, the econometrical instrument of time series was used, such as Error-Correction Vector (VEC) and cointegration techniques. The estimation results suggest an export-led growth model, as well as evidence of productivity-enhancing effects of industrial exports and of productivity limiting effects of ore exports. The continuous growth of the Chilean economy, based in the exporting sector intensive in natural resources and the stability that the economy presented, even during the turbulent decade of 1990 makes Chile an important object of study for the relations between international trade and economic growth